Distributional Implications of the VAT Reform in the Philippines - Newhouse, David Locke (IMF Working Papers; Working Paper ;, 2007)
This paper assesses the distributional impact of the recent VAT reform in the Philippines and evaluates alternative methods to mitigate the effects of the reform on poor households. The reform was progressive and relatively well targeted. To alleviate the impact of the reform on the poor, several mitigating measures were introduced. Although these measures reduced the adverse impact of the VAT reform for all households, a sizable amount of the benefit accrued to high-income households. Targeted transfer schemes have the potential to deliver a much higher percentage of benefits to the poor.